Synthesis of novel 5-substituted 2-pyrazolylthiazol-4-ones as potential bioligically active compounds - I. M. Yushyn; A. V. Lozynskyi; O.-M. V. Fedusevych; O. Yа. Vovchuk; R. B. Lesyk (Zaporozhye State Medical University, 2020)
One of the effective strategies in potential "drug-like" molecules design is using a molecular hybridization approach based on the combination of several pharmacological scaffolds in one molecule. The main argument for using this approach is a polypharmacological theory based on the interaction of mentioned hybrid molecules with multiple bio-targets based on selectivity and the resulting reduction of toxicity. The aim of the work is to synthesize a number of new 5-substituted 2-pyrazolylthiazol-4-ones as potentional biologically active compounds. Materials and methods. Organic synthesis, 1H NMR spectroscopy. Results. The synthesis of new 5-ene-2-pyrazolylthiazol-4-ones was carried out via a three-component [2+3]-cyclocondensation reaction of 3-methyl-5-aryl-4,5-dihydropyrazole-1-carbothiamides with chloroacetic acid and the corresponding carbonyl compounds in acetic acid medium. The structure of the synthesized compounds was confirmed by elemental analysis and 1H NMR spectroscopy. Conclusions. As a result of chemical transformations, a library of new thiazole-pyrazoline conjugates was synthesized based on a hybrid-pharmacophore approach to further anticancer activity evaluation within the DTP NCI protocol.